Is Old Money Better than New? Duration and Monetary Regimes - Andrew K. Rose; Ilian Mihov (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
We compare the duration and performance of different monetary regimes, especially the contrast between countries those that fix exchange rates and those that target inflation. Inflation targeting is a more durable policy; no country has yet been forced to abandon an inflation target, while many have abandoned fixed exchange rates. Indeed, even though inflation targeting began only in 1990, the duration of inflation targeting regimes is at least as long as, or longer than all alternative monetary regimes for comparable countries. Regime duration also matters in monetary policy; older regimes are typically more successful than younger ones in achieving low inflation.
Keywords: E52; E58; 330; Empirical; panel; exchange; rate; inflation; policy; data; success; target; filter; time; Fester Wechselkurs; Inflation Targeting; Wechselkurssystem; Dauer; Geldpolitik; Welt